Effects of iron nano-particle’s on expression of tetracycline resistance encoding genes in Staphylococcus aureus by Real Time-PCR - ARAB, H.; SHOJAEE SADI, B.; AMINI, K. (Journal of the Hellenic Veterinary Medical Society, 2018)
Increasing bacterial resistance towards traditional/conventional antibiotics is a major global health concern worldwide. Iron oxide nanoparticles (Fe nanoparticles, with average size of 20 nm) have considerable potential as antimicrobial agents in food safety applications due to their structure, surface properties, and stability. The aim of this work was to investigate the antibacterial effects and mechanism of action of iron nanoparticles against the expression of the tetA gene in Tetracycline Resistant Staphylococcus aureus strains by real time PCR. In the cross-sectional study, a total of 60 S. aureus were collected. Antibiotic susceptibility test was performed on the muller hinton agar according to the Clinical and Laboratory Standards Institute (CLSI). Then all strains were evaluated for tetA, tetB, tetC and tetD genes by multiplex-PCR method. In-vitro activity of iron oxide nanoparticles was evaluated against all resistant strains by microbroth dilution method. Therefore, the expression of tetA gene was measured in treated with iron oxide nanoparticles and untreated resistant S. aureus strain by Real time PCR. Our results indicated 25 (41.66%) strains resistant to Tetracycline. The prevalence of tetA, tetB, tetC and tetD genes were 5 (8.33%), 2 (2.33%), 20 (33.33%) and 10 (10.67%), respectively. The expression of tetA genes in resistant S. aureus strains treated with Iron oxide nanoparticles was lower than the untreated isolates. Iron oxide nanoparticles have strong antibacterial activity against resistant to Tetracycline S. aureus strains. In addition to, these nanoparticles reduce the expression of antibiotic resistance gene.